MRI in Diagnosis of a Giant Prostatic Utricle. (15th July 2014) - Johnson, Dustin; Parikh, Kushal; Schey, William; Mar, Winnie
Abstract : A prostatic utricle cyst is an epithelial lined diverticulum arising from the prostatic urethra and usually asymptomatic when small. When enlarged, it may be symptomatic and is typically accompanied by hypospadias. We present a case of a markedly enlarged prostatic utricle in a neonate without hypospadias, demonstrated on voiding cystourethrography (VCUG), ultrasound, and 1.5 Tesla MRI.